Judicial Errors and Crime Deterrence: Theory and Experimental Evidence - Luca Stanca
The standard economic theory of crime deterrence predicts that the conviction of an innocent (type-I error) is as detrimental to deterrence as the acquittal of a guilty individual (type-II error). In this paper, we qualify this result theoretically, showing that in the presence of risk aversion, loss-aversion, or differential sensitivity to procedural fairness, type-I errors can have a larger effect on deterrence than type-II errors. We test these predictions with an experiment where participants make a decision on whether to steal from other individuals, being subject to different probabilities of judicial errors. The results indicate that both types of judicial errors have a large and significant impact on deterrence, but these effects are not symmetric. An increase in the probability of type-I errors has a larger negative impact on deterrence than an equivalent increase in the probability of type-II errors. This asymmetry is largely explained by risk aversion and, to a lesser extent, type-I error aversion.Judicial errors, criminal procedure, procedural fairness, experimental economics, law and economics, crime, deterrence